Efficient chromium (VI) removal from wastewater by adsorption-assisted photocatalysis using MXene - Jamaluddin, Nur Shafiqah (Elsevier Ltd., 2022)
Hexavalent chromium, Cr(VI), is considered hazardous heavy metal in water bodies that can cause severe effects on human health and the environment. Over the years, myriad attention has been focused on developing photocatalysts to remove Cr(VI) from wastewater. However, broad bandgap energy and the high electron recombination rate of these conventional photocatalysts have limited their photocatalytic ability. Therefore, efficient photocatalytic materials for Cr(VI) removal in wastewater is strongly demanded. In this study, delaminated MXene was successfully synthesised and used to remove Cr(IV) from the aqueous solution. The synthesised delaminated MXene was characterised using XRD, EDX, FTIR, FESEM, nitrogen adsorption-desorption analysis, TGA, UV-Vis-NIR spectroscopy and XPS. Based on the results, the optimum operating conditions for Cr(VI) removal by the synthesised MXene was obtained at pH 4 with photocatalyst loading of 1.5 g/L and Cr(VI) initial concentration of 5 mg/L. The removal efficiency of Cr(VI) via adsorption-assisted photocatalysis over various concentrations was around 3.1-28.9% higher than adsorption, verifying a synergistic effect of adsorption and photocatalysis by the delaminated MXene. The isotherm of Cr(VI) adsorption was fitted by the Langmuir model (R2 > 0.9848) and was found better than the Freundlich model (R2 > 0.8824). Meanwhile, the time dependence of Cr(VI) adsorption was well fitted to the pseudo-second-order kinetic model with R2 > 0.9999. In conclusion, the results obtained suggest that the delaminated MXene possesses excellent properties and the ability to remove Cr(VI) via adsorption-assisted photocatalysis and has great potential to be used for industrial wastewater applications.